Analisis Komunikasi Interpersonal dan Pengaruhnya Terhadap Kesehatan Mental dalam Drama Daily Dose Of Sunshine - Marbun, Andre Samuel William; Khairullah, Khairullah (Mahesa Research Center, 2025)
This study aims to analyze the representation of interpersonal communication in the Korean drama Daily Dose of Sunshine and its relevance to mental health issues. The approach used is qualitative with a literature study method, with primary data sources in the form of 12 key scenes that show the dynamics of communication between the main character, Jung Da Eun, with patients, family, and colleagues. The analysis is carried out through open coding techniques and thematic analysis, as well as interpretive-narrative approaches to uncover the meaning of empathic communication, social support, stigma, and emotional expression. The results of the study show that interpersonal communication has an important role in the psychological recovery process, both as a means of building trust and as a bridge in reconstructing post-traumatic stress disorder. On the other hand, communication that is full of stigma and domination worsens the mental state of the character. The drama not only illustrates the importance of communication between patients and medical personnel but also highlights the need for emotional support for healthcare workers themselves. These findings confirm that empathetic and reflective interpersonal communication can be the foundation for creating an inclusive and supportive environment for mental health recovery.